Pharmacokinetic interactions and safety evaluations of coadministered tafenoquine and chloroquine in healthy subjects. (December 2013) - Miller, Ann K.; Harrell, Emma; Ye, Li; Baptiste‐Brown, Sharon; Kleim, Jőrg‐Peter; Ohrt, Colin; Duparc, Stephan; Möhrle, Jörg J.; Webster, Alison; Stinnett, Sandra; Hughes, Arlene; Griffith, Sandy; et al.
<x xml:space="preserve">Abstract</x> Aims The long‐acting 8‐aminoquinoline tafenoquine (TQ) coadministered with chloroquine (CQ) may radically cure Plasmodium vivax malaria. Coadministration therapy was evaluated for a pharmacokinetic interaction and for pharmacodynamic, safety and tolerability characteristics. Methods Healthy subjects, 18–55 years old, without documented glucose‐6‐phosphate dehydrogenase deficiency, received CQ alone (days 1–2, 600 mg; and day 3, 300 mg), TQ alone (days 2 and 3, 450 mg) or coadministration therapy (day 1, CQ 600 mg; day 2, CQ 600 mg + TQ 450 mg; and day 3, CQ 300 mg + TQ 450 mg) in a randomized, double‐blind, parallel‐group study. Blood samples for pharmacokinetic and pharmacodynamic analyses and safety data, including electrocardiograms, were collected for 56 days. Results The coadministration of CQ + TQ had no effect on TQ AUC0–t, AUC0–∞, Tmax or t1/2. The 90% confidence intervals of CQ + TQ vs. TQ for AUC0–t, AUC0–∞ and t1/2 indicated no drug interaction. On day 2 of CQ + TQ coadministration, TQ Cmax and AUC0–24 increased by 38% (90% confidence interval 1.27, 1.64) and 24% (90% confidence interval 1.04, 1.46), respectively. The pharmacokinetics of CQ and its primary metabolite desethylchloroquine were not affected by TQ. Coadministration had no clinically significant effect on QT intervals and was well tolerated. Conclusions No clinically significant safety or pharmacokinetic/pharmacodynamic interactions were observed with coadministered CQ and TQ in healthy subjects.